A review on the consumption of vended fruits: microbial assessment, risk, and its control. Issue 2 (21st April 2020) - Igiehon, Oluwakemi Osarumwense; Adekoya, Ademola Ezekiel; Idowu, Anthony Temitope
Abstract: Fruits are very beneficial to health and their consumption has been recommended in daily diets. However, when fresh fruits are harvested and processed into sliced ready-to-eat or vended forms for sale, hygienic procedures are neglected. Thus, they are easily infested by pathogens. In addition, uneducated vendors who sell these fruits often display or hawk them on the streets in contaminated containers, utensils, or dirty environments. This poses a great threat to the health of consumers. In the light of this realization, some microbial assessments have been carried out to ascertain the safety of these vended fruits, thus making it a necessity to exploit the outcomes of some of these microbial assessments on vended fruits in order to sensitize the consumers on the effect of their consumption and mitigate risk by improving their quality. This will assist to lower certain health concerns, an outbreak of diseases, and death.